Asuhan Kebidanan Berkelanjutan (Continuity Of Care) Pada Ny. A di PMB Nur'aini Munasiroh Jepara: Asuhan Kebidanan Berkelanjutan (Continuity Of Care) Pada Ny. A di PMB Nur'aini Munasiroh Jepara - Nashiroh, Lailatun; Zubaidah; Windyarti, Mei Lia Nindya Zulis (Lentera Ilmu Madani, 2023)
ABSTRACT The success of the maternal health program can be assessed through the main indicators of the Maternal Mortality Rate (MMR) and the Infant Mortality Rate (IMR). Efforts to accelerate the reduction of MMR and IMR are carried out by midwives as health workers according to their duties and functions who can provide ongoing services and checks to reduce MMR and IMR. Case study approach with descriptive observational. During her pregnancy Mrs. A made 6 visits and during the third trimester Mrs. A experienced swelling in her legs, back pain and complaints of frequent urination. Therefore, she was advised to drink lots of water during the day and drink less water in the afternoon. The mother advised her to get enough rest and take a light walk in the morning or evening. Spontaneous delivery process assisted by normal delivery care (APN) 58 steps went smoothly Caring for newborns and the postpartum period was smooth and within normal limits. Continuing midwifery care that is provided on an ongoing basis in accordance with existing theories. Keywords: Continuity of Care; Emesis Garavidarum;Midwifery